Examining the transcription factor FOXO1 and its regulation by glucocorticoids and inflammatory mediators in hepatic insulin signalling - Visser, Ankia (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.